Amartya Sen's nonideal theory. Issue 2 (13th December 2019) - Meshelski, Kristina
ABSTRACT: Amartya Sen argues that Rawls's theory is not only unnecessary in the pursuit of justice, but it may even be an impediment to justice in so far as it has discouraged more useful work. Against what he considers the dominance of transcendental theory, Sen calls for a more realistic and practical 'comparative' theory of justice. Sen's negative point has been widely discussed, but here I develop a reconstruction of Sen's positive theory (a combination of Adam Smith's Impartial Spectator, Social Choice Theory, and the Capabilities Approach) in order to evaluate it on its own terms. I find that the theory is technocratic, despite Sen's insistence to the contrary.